2008
DOI: 10.1111/j.1365-2966.2007.12725.x
|View full text |Cite
|
Sign up to set email alerts
|

The Monitor project: rotation of low-mass stars in NGC 2362 – testing the disc regulation paradigm at 5 Myr

Abstract: International audienceWe report on the results of a time-series photometric survey of NGC 2362, carried out using the CTIO 4-m Blanco telescope and Mosaic-II detector as part of the Monitor project. Rotation periods were derived for 271 candidate cluster members over the mass range 0.1 <~ M/Msolar <~ 1.2. The rotation period distributions show a clear mass-dependent morphology, qualitatively similar to that in NGC 2264, as would be expected from the age of this cluster. Using models of angular momentum evoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(154 citation statements)
references
References 35 publications
(73 reference statements)
10
144
0
Order By: Relevance
“…Irwin et al (2008) did not find such a correlation between rotational period and amplitude of the modulation in the 5 Myr old cluster NGC 2362. It is worth to note that their sample only extends down to about 0.1 M , with a high fraction of objects even more masive than 0.4 M .…”
Section: Rotational Period and Ptp Amplitude Correlation In The Onc Amentioning
confidence: 70%
See 1 more Smart Citation
“…Irwin et al (2008) did not find such a correlation between rotational period and amplitude of the modulation in the 5 Myr old cluster NGC 2362. It is worth to note that their sample only extends down to about 0.1 M , with a high fraction of objects even more masive than 0.4 M .…”
Section: Rotational Period and Ptp Amplitude Correlation In The Onc Amentioning
confidence: 70%
“…Several authors have investigated the rotational properties of solar mass and low mass stars in clusters of various ages (e.g. Stauffer & Hartmann 1987;Prosser et al 1993Prosser et al , 1995Terndrup et al 2000;Scholz & Eislöffel 2004b;Irwin et al 2008). In young clusters and star forming regions, an enormous spread in rotational periods has been observed at all stellar masses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This trend has been hinted at previously by Dahm et al (2012) using v sin is, and by Scholz et al (2015) for brown dwarfs, but have been conclusively demonstrated in this paper. It is also evident in other young clusters such as the Orion Nebula Cluster (Herbst et al 2001), NGC2264 (Lamm et al 2005), NGC2362 (Irwin et al 2008a), and σOri (Cody & Hillenbrand 2010), among others. Despite its ubiquity, its origin and evolution remain unclear and appear contradictory at times.…”
Section: Discussionmentioning
confidence: 87%
“…Irwin et al (2008) suggest that this varying slope for masses between 0.1-0.5M was a result of cluster evolution with age.…”
Section: Cygob2 Inside the Picture Of Pms Rotational Evolutionmentioning
confidence: 85%